Antibacterial mechanism of lactic acid on physiological and morphological properties of Salmonella Enteritidis, Escherichia coli and Listeria monocytogenes. (January 2015) - Wang, Chenjie; Chang, Tong; Yang, Hong; Cui, Min
Abstract: Lactic acid is widely used to inhibit the growth of important microbial pathogens, but its antibacterial mechanism is not yet fully understood. The objective of this study was to investigate the antibacterial mechanism of lactic acid on Salmonella Enteritidis, Escherichia coli and Listeria monocytogenes by size measurement, TEM, and SDS-PAGE analysis. The results indicated that 0.5% lactic acid could completely inhibit the growth of Salmonella Enteritidis, E. coli and L. monocytogenes cells. Meanwhile, lactic acid resulted in leakage of proteins of Salmonella, E. coli and Listeria cells, and the amount of leakage after 6 h exposure were up to 11.36, 11.76 and 16.29 μg/mL, respectively. Measurements of the release of proteins and SDS-PAGE confirmed the disruptive action of lactic acid on cytoplasmic membrane, as well as the content and activity of bacterial proteins. The Z-Average sizes of three pathogens were changed to smaller after lactic acid treatment. The damaged membrane structure and intracellular structure induced by lactic acid could be observed from TEM images. The results suggested that the antimicrobial effect was probably caused by physiological and morphological changes in bacterial cells. Highlights: Pathogens could be completely inactivated after exposure to lactic acid. Lactic acid resulted in great leakage of protein of three pathogens. Bacterial protein bands of lactic acid-treated cells got fainter or disappeared. Z-Average sizes of pathogens were changed to smaller after lactic acid treatment. Lactic acid caused collapsed or even broken cells with obvious pits and gaps.